2019
DOI: 10.1093/biolre/ioz127
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor-1 beta protects endometriotic cells against apoptotic cell death by up-regulating the expression of antiapoptotic genes†

Abstract: The overexpression of hepatocyte nuclear factor-1 beta (HNF1β) in endometriotic lesion has been demonstrated. However, the role of HNF1β in endometriosis remains largely unknown. Human endometriotic 12Z cells showed higher level of HNF1β when compared with normal endometrial HES cells. In human endometriotic 12Z cells, HNF1β knockdown increased susceptibility to apoptotic cell death by oxidative stress, while HNF1β overexpression suppressed apoptosis. In addition, HNF1β knockdown and overexpression significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Notably, most NF-κB-related endometriosis studies chose normal/ectopic endometrial stromal cells for subsequent experiments. However, several studies also revealed that the role of NF-κB in endometrial epithelial cells shares several similarities with its role in endometrial stromal cells, such as the regulation by TNFα, estrogen signaling, and ncRNAs [24,31,61]; the promotion of cell proliferation, migration, invasion, and adhesion [56,73,74]; and the contribution to the resistance of ROS stress-induced cell apoptosis [56]. In addition, several drugs exert anti-endometriotic effects by downregulating NF-κB expression in endometrial epithelial cells [67,93,[117][118][119].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, most NF-κB-related endometriosis studies chose normal/ectopic endometrial stromal cells for subsequent experiments. However, several studies also revealed that the role of NF-κB in endometrial epithelial cells shares several similarities with its role in endometrial stromal cells, such as the regulation by TNFα, estrogen signaling, and ncRNAs [24,31,61]; the promotion of cell proliferation, migration, invasion, and adhesion [56,73,74]; and the contribution to the resistance of ROS stress-induced cell apoptosis [56]. In addition, several drugs exert anti-endometriotic effects by downregulating NF-κB expression in endometrial epithelial cells [67,93,[117][118][119].…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload activates IKKβ and stimulates NF-κB signaling, conferring pro-endometriotic behaviors on endometrial stromal cells 27 . Hepatocyte nuclear factor-1 beta (HNF1β) is a homeobox transcription factor that is overexpressed in endometriotic cells 56 . It functions as a coactivator for NF-κB, and its activation can enhance the survivability of endometriotic cells in oxidative cellular environments 56 .…”
Section: Regulation Of Nf-κb Signaling In Endometriosismentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the survival and apoptosis-related genes were upregulated or downregulated in the previous studies cited. Thus, the proliferation-and growth-related genes, including IGF1 (16)(17)(18)(19), IGF2 (19), vascular endothelial growth factor (VEGF) (40)(41)(42), hepatocyte growth factor (HGF) (43)(44)(45), nerve growth factor (NGF) (46)(47)(48), platelet-derived growth factor (PDGF) (16,49), epidermal growth factor receptor (EGFR) (16,17,49,50), fibroblast growth factor 2 (FGF2) (49,51,52) and mechanistic target of rapamycin kinase (mTOR) (53,54), were upregulated in both the ectopic and eutopic endometria from subjects with adenomyosis compared with the eutopic endometria from women without adenomyosis, while the anti-apoptotic or autophagy-related genes, such as BCL2 apoptosis regulator (BCL2) (38,(55)(56)(57), beclin 1 (BECN1) (58,59) and programmed cell death 4 (PDCD4) (60,61), were much higher in the ectopic and eutopic endometria than in the control endometria. Furthermore, the decreased expression of BCL2 associated X, apoptosis regulator (BAX) has been observed in adenomyosis, suggesting that the downregulation of apoptotic cell death machinery is a hallmark of adenomyosis (39).…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%